Flexural cracking behavior and crack width predictions of composite (steel + UHPC) lightweight deck system. (1st September 2019) - Luo, Jun; Shao, Xudong; Fan, Wei; Cao, Junhui; Deng, Shuwen
Highlights: The crack propagations and patterns are described. Presence of reinforcement bars has a significant influence on cracking behavior. Influences of primary design parameters on cracking behavior are discussed. Equations for estimating the reinforcement stress are developed. Analytical model for predicting crack width is proposed. Abstract: This paper aims to clarify flexural cracking behaviors (e.g., crack width and crack spacing) of a lightweight deck system composed of steel orthotropic deck and thin ultra-high performance concrete (UHPC) layer. Forty steel-UHPC composite plates and eight steel-UHPC composite beams were tested to explore their cracking characteristics in transverse and longitudinal directions, respectively. The influences of reinforcement ratios, the thickness of the UHPC cover, the spacing of stud shear connectors, and the depth of the UHPC layers on cracking behaviors were examined. According to the bridges with composite deck systems recently constructed in China, the same spacing of reinforcing bars were employed in longitudinal and transverse directions, which ranged from 30 and 75 mm. The test results show that the occurrence and growth of cracks in UHPC layers could be effectively restricted by increasing reinforcement ratios, reducing the thickness of UHPC cover and the spacing of stud shear connectors, as well as thickening the UHPC layer. For the average crack spacing, the most significant factor was the reinforcement ratio. For the longitudinal behavior of the lightweight deck system, the steel-UHPC composite beams would fail due to the yield of steel U-ribs and the crack width in the UHPC layer would be small (e.g., 0.09–0.14 mm) when the reinforcement ratio and the thickness of UHPC cover are design appropriately. Based on the experimental observations, the formulas were developed to estimate the stress in reinforcements for the composite (steel + UHPC) lightweight deck system. The reinforcement stresses predicted by these formulas were in agreement with the experimental data. A new formulation for predicting the maximum crack width in composite (steel + UHPC) lightweight deck system was also proposed. Good agreements were achieved between the test results and the predicted values of the flexural crack width.